2004
DOI: 10.1111/j.1432-2277.2004.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic haemangioendothelioma in adults: excellent outcome following liver transplantation

Abstract: Hepatic epithelioid haemangioendotheliomas (HEHEs) are rare, low-grade vascular tumours. transplantation Five adults with HEHEs and one adult with a vascular tumour showing combined features of haemangioma and haemangioendothelioma underwent liver transplantation. Two HEHE patients had extrahepatic metastases at the time of transplantation. Median survival time following diagnosis was 10.7 years (range 40 months to 195 months). One patient needed resection of a HEHE in the breast 13 years post-transplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 22 publications
1
21
0
5
Order By: Relevance
“…Our results are consistent with those previously published by Madariaga et al [17] who reported 71% actuarial patient survival and 60% actuarial disease-free survival at 5 years postOLT in 16 patients and those reported by Yokoyama et al [24] with an actuarial survival rates of 88% and 48% disease-free in eight patients treated by OLT at 5 years. Penn et al [22] also reported 7 out of 21 patients who developed HEHE recurrences and 43% posttransplantation survival rate at 5 years and in Lerut et al [25] study, an excellent outcome following LT was obtained in six patients with disease-free survival at a range of 22 months-14 years. More recently, results of the largest reported multicenter transplant series, including 59 patients, were found to be excellent with 1-, 5-, and 10 year patient survival rates of 93%, 83%, and 72%, respectively [26].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our results are consistent with those previously published by Madariaga et al [17] who reported 71% actuarial patient survival and 60% actuarial disease-free survival at 5 years postOLT in 16 patients and those reported by Yokoyama et al [24] with an actuarial survival rates of 88% and 48% disease-free in eight patients treated by OLT at 5 years. Penn et al [22] also reported 7 out of 21 patients who developed HEHE recurrences and 43% posttransplantation survival rate at 5 years and in Lerut et al [25] study, an excellent outcome following LT was obtained in six patients with disease-free survival at a range of 22 months-14 years. More recently, results of the largest reported multicenter transplant series, including 59 patients, were found to be excellent with 1-, 5-, and 10 year patient survival rates of 93%, 83%, and 72%, respectively [26].…”
Section: Discussionmentioning
confidence: 89%
“…According to the reported experience in the revelant literature, limited extrahepatic disease, such as small pulmonary metastases should not be currently considered as an absolute contraindication to OLT [22,25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, with such wide biologic characteristics, it is difficult to evaluate the effectiveness of a particular treatment. Previous studies suggest that extrahepatic metastasis is not a prognostic factor after liver transplantation for EH; 2,4,[8][9][10][11][12]14 however, it is paradoxical that the presence of metastasis at transplantation would be associated with better post-transplant prognosis for a malignant disease.To re-evaluate the clinical effectiveness of liver transplantation for EH, we reviewed 13 studies 4,6-16 documenting long-term results after liver transplantation for EH. Of the 41 patients studied, including our patient Abstract Epithelioid hemangioendothelioma (EH) of the liver is a rare tumor, generally considered to have low-grade malignancy.…”
mentioning
confidence: 95%
“…This is a rare, low-grade vascular malignancy whose therapeutic algorithm is far from standardized. 1,2 As demonstrated by different authors, [3][4][5][6] liver transplantation is a valuable treatment for hepatic epithelioid hemangioendothelioma, even in cases of extrahepatic metastasis. In our case, the 26-year-old donor and the 26-year-old recipient were twins (brother and sister, respectively).…”
mentioning
confidence: 98%